2013
DOI: 10.1016/j.nbd.2013.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Ca2+-dependent glutamate release from astrocytes of the BACHD Huntington's disease mouse model

Abstract: Huntington’s disease (HD) causes preferential loss of a subset of neurons in the brain although the huntingtin protein is expressed broadly in various neural cell types, including astrocytes. Glutamate-mediated excitotoxicity is thought to cause selective neuronal injury, and brain astrocytes have a central role in regulating extracellular glutamate. To determine whether full-length mutant huntingtin expression causes a cell-autonomous phenotype and perturbs astrocyte gliotransmitter release, we studied cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 57 publications
(91 reference statements)
2
44
0
Order By: Relevance
“…Experimental increase in GLT-1 expression in astrocytes expressing mhtt by a lentiviral vector decreased astroglial reactivity (Faideau et al ., 2010), while treatment of R6/2 mice with ceftriaxone increased GLT-1 expression and improved motor symptoms (Faideau et al ., 2010). Astrocytes may also contribute to excitotoxicity in HD context through increased glutamate release, which indeed was found in astroglial cells isolated from the cortex of the BACHD mouse model (Lee et al ., 2013); this enhancement of glutamate release was linked to an increased expression of pyruvate carboxylate and hence an increased de novo production of glutamate. Besides compromised regulation of extracellular glutamate, astrocytes also display compromised potassium buffering, as recently demonstrated in HD mouse R6/2 and Q175 models (Tong et al, 2014).…”
Section: Neurodegenerative Diseasesmentioning
confidence: 83%
“…Experimental increase in GLT-1 expression in astrocytes expressing mhtt by a lentiviral vector decreased astroglial reactivity (Faideau et al ., 2010), while treatment of R6/2 mice with ceftriaxone increased GLT-1 expression and improved motor symptoms (Faideau et al ., 2010). Astrocytes may also contribute to excitotoxicity in HD context through increased glutamate release, which indeed was found in astroglial cells isolated from the cortex of the BACHD mouse model (Lee et al ., 2013); this enhancement of glutamate release was linked to an increased expression of pyruvate carboxylate and hence an increased de novo production of glutamate. Besides compromised regulation of extracellular glutamate, astrocytes also display compromised potassium buffering, as recently demonstrated in HD mouse R6/2 and Q175 models (Tong et al, 2014).…”
Section: Neurodegenerative Diseasesmentioning
confidence: 83%
“…The onset of Huntington's disease (HD) symptoms in mouse was found to be causally related to decreased expression of Kir4.1 channel (Tong et al, 2014), and was associated with excessive Ca 2+ -dependent astrocytic Glu release (Lee et al, 2013). In this light, the role of astrocytic NMDA receptors in the development of HD deserves to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of polyQ-expanded htt by mouse striatal astrocytes was shown to impair glutamate transport (Faideau et al 2010), and enhanced calcium-dependent glutamate release has also been shown from astrocytes of an alternative mouse model of HD (Lee et al 2013b). The transport of other neurotransmitters may also be affected-the loss of astrocytic GABA release through GAT-3 has been implicated in reduced tonic inhibition in striatal output neurons from HD mice (Wojtowicz et al 2013).…”
Section: Astrocytes In Hdmentioning
confidence: 99%